Airway management during left-sided gastrobronchial fistula repair after esophagectomy for esophageal carcinoma: A case report. Issue 35 (3rd September 2021) - Wang, Sih-Yu; Yuan, Wei-Chin; Wu, En-Bo
Abstract: Rationale: Gastrobronchial fistula (GBF) is a rare but life-threatening complication of esophagectomy with gastric conduit reconstruction, and airway management during fistula repair is challenging. Here, we describe airway management in a patient undergoing left-sided GBF repair using video-assisted thoracoscopic surgery. Patient concerns: A 63-year-old man diagnosed with esophageal carcinoma underwent esophagectomy with reconstruction by gastric pull-up and tabularization of the gastric conduit. Subsequently, about 8 weeks later, the patient presented with repeated pneumonia and a 1-week history of cough with significant sputum, dysphagia, and repeated fever. Diagnosis: GBF, a rare postoperative complication, was located on the left main bronchus at 2 cm below the carina and was diagnosed based on findings from gastroscopy, flexible bronchoscopy, and thoracic computed tomography scan with contrast. Interventions: We performed left-sided one-lung ventilation (OLV) under total intravenous anesthesia instead of inhalational anesthetics. The left-sided OLV, with positive end-expiratory pressure (PEEP) and nasogastric tube decompression, generated positive pressure across the fistula. It prevented backflow into the left main bronchus. Total intravenous anesthesia preserved hypoxic pulmonary vasoconstriction and prevented adverse effects associated with inhalational anesthetics. A right-sided, double-lumen endotracheal tube was inserted after anesthesia induction, and surgical repair was performed through a right-sided video-assisted thoracoscopic surgery. Outcomes: Intraoperative hemodynamics remained relatively stable, except for brief tachycardia at 113 beats/min. Arterial blood gas analysis revealed pH 7.17 and PaO2 89.1 mmHg upon 100% oxygenation, along with hypercapnia (PaCO2 77.1 mmHg), indicating respiratory acidosis. During OLV, pulse oximetry remained higher than 92%. The defect in the left main bronchus was successfully sutured after dissecting the fistula between the left main bronchus and the gastric conduit, and subsequently, OLV resulted in ideal ventilation. Lessons: A left-sided GBF could lead to leakage from the OLV during surgery. Possible aspiration or alveolar hypoventilation due to this leakage is a major concern during airway management before surgical repair of the main bronchus.